Description of Komagataeibacter melaceti sp. nov. and Komagataeibacter melomenusus sp. nov. Isolated from Apple Cider Vinegar - Leon Marič; Ilse Cleenwerck; Tomaž Accetto; Peter Vandamme; Janja Trček (Microorganisms, 2020)
Two novel strains AV382 and AV436 were isolated from a submerged industrial bioreactor for production of apple cider vinegar in Kopivnik (Slovenia). Both strains showed very high (≥98.2%) 16S rRNA gene sequence similarities with Komagataeibacter species, but lower 16S–23S rRNA gene internal transcribed spacer (ITS). The highest similarity of the 16S–23S rRNA gene ITS of AV382 was to Komagataeibacter kakiaceti LMG 26206T (91.6%), of AV436 to Komagataeibacter xylinus LMG 1515T (93.9%). The analysis of genome sequences confirmed that AV382 is the most closely related to K. kakiaceti (ANIb 88.2%) and AV436 to K. xylinus (ANIb 91.6%). Genome to genome distance calculations exhibit for both strains ≤47.3% similarity to all type strains of the genus Komagataeibacter. The strain AV382 can be differentiated from its closest relatives K. kakiaceti and Komagataeibacter saccharivorans by its ability to form 2-keto and 5-keto-D-gluconic acids from glucose, incapability to grow in the presence of 30% glucose, formation of C19:0 cyclo ω8c fatty acid and tolerance of up to 5% acetic acid in the presence of ethanol. The strain AV436 can be differentiated from its closest relatives K. xylinus, Komagataeibacter sucrofermentans, and Komagataeibacter nataicola by its ability to form 5-keto-D-gluconic acid, growth on 1-propanol, efficient synthesis of cellulose, and tolerance to up to 5% acetic acid in the presence ethanol. The major fatty acid of both strains is C18:1ω7c. Based on a combination of phenotypic, chemotaxonomic and phylogenetic features, the strains AV382T and AV436T represent novel species of the genus Komagataeibacter, for which the names Komagataeibactermelaceti sp. nov. and Komagataeibacter melomenusus are proposed, respectively. The type strain of Komagataeibacter melaceti is AV382T (= ZIM B1054T = LMG 31303T = CCM 8958T) and of Komagataeibacter melomenusus AV436T (= ZIM B1056T = LMG 31304T = CCM 8959T).